2018
DOI: 10.1111/jgh.14472
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a novel predictor of venous thromboembolic complications in inflammatory bowel disease with current predictors

Abstract: In hospitalized patients with IBD, D-dimer values were highly associated with VTE onset. Therefore, measurement of D-dimer values on admission is critical for the management of thromboembolic complications in patients with IBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…To date, several retrospective cohort studies ( 24 29 ) have attempted to evaluate the effect of acquired risk factors on the incidence of venous thromboembolic events in inflammatory bowel disease patients with controversial results. For instance, while some studies had reported a significantly increased risk in aging inflammatory bowel disease patients ( 24 , 27 , 30 ), other studies did not report this outcome ( 28 , 31 , 32 ). Similarly, there is still a lack of consensus regarding the risks of venous thromboembolism associated with steroid therapy, surgery, obesity in patients with inflammatory bowel disease ( 24 , 28 , 29 , 33 35 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, several retrospective cohort studies ( 24 29 ) have attempted to evaluate the effect of acquired risk factors on the incidence of venous thromboembolic events in inflammatory bowel disease patients with controversial results. For instance, while some studies had reported a significantly increased risk in aging inflammatory bowel disease patients ( 24 , 27 , 30 ), other studies did not report this outcome ( 28 , 31 , 32 ). Similarly, there is still a lack of consensus regarding the risks of venous thromboembolism associated with steroid therapy, surgery, obesity in patients with inflammatory bowel disease ( 24 , 28 , 29 , 33 35 ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, while some studies had reported a significantly increased risk in aging inflammatory bowel disease patients ( 24 , 27 , 30 ), other studies did not report this outcome ( 28 , 31 , 32 ). Similarly, there is still a lack of consensus regarding the risks of venous thromboembolism associated with steroid therapy, surgery, obesity in patients with inflammatory bowel disease ( 24 , 28 , 29 , 33 35 ). To the best of our knowledge, there are no systematic reviews or meta-analyses that summarized the existing data, evaluating risk factors that can influence the incidence of venous thromboembolism in patients with inflammatory bowel disease.…”
Section: Introductionmentioning
confidence: 99%
“…Elevated D-dimer values was an independent risk factor for thromboembolism in IBD. Case report also showed predictive value of D-dimer in CVST [10,11] . Role of medical treatment for IBD was in controversial.…”
Section: Discussionmentioning
confidence: 64%
“…A recent study showed elevated D-dimer at admission was highly predictive for venous thrombosis and therefore D-dimer test might be a useful screening tool. 24 However, another study suggested that the utility of D-dimer tests as screening methods could be limited, since elevated D-dimer is common in inflammatory diseases. Therefore, though D-dimer test is economical for initial screening, direct imaging study might be more appropriate for patients with high risks.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, the modality of screening was mainly D-dimer tests, with less than 3% of patients receiving ultrasound screening or computed tomography scans. A recent study showed elevated D-dimer at admission was highly predictive for venous thrombosis and therefore D-dimer test might be a useful screening tool [ 24 ]. However, another study suggested that the utility of D-dimer tests as screening methods could be limited, since elevated D-dimer is common in inflammatory diseases.…”
Section: Discussionmentioning
confidence: 99%